Online Teaching in Management Education: A Case Study of Janakpurdham - Shah, Binod; Tiwari, Uday Kishor (Journal of Management, 2023)
This research paper explores the effectiveness, challenges, and opportunities of online teaching in the context of management education in Janakpurdham, Nepal. In this study, a survey method of research design has been employed. The nature of this study is a descriptive and survey research. Questionnaire method has been used to collect the data from students and faculty members. The study has been done by convenient sampling method. The findings reveal that both faculty members and students perceive online teaching as equally effective as traditional face-to-face teaching in management education. The benefits of online teaching, such as flexibility, access to diverse resources, and opportunities for global collaborations, are acknowledged. However, challenges related to limited face-to-face interactions, maintaining student engagement, and technical issues are identified. The research highlights the significance of faculty training and support in adapting to online teaching methods. The study also offers recommendations to improve online teaching practices in management education in Janakpurdham, emphasizing interactive pedagogical strategies, technological readiness, and incorporating student feedback into course design.